Thermal- structure Coupling Effect and Analysis of Gear Transmission - Wang Wei; Li Jianmin; Chen Huanguo; Pan Xiaodong; Sun Bin; Zhou Xinteng; Lin Feng (Jixie chuandong)
The relative friction surface in the process of the heavy duty gear transmission will generate a lot of heat cause tooth surface temperature rising,increased stress,reduced reliability,but the heat flow boundary load area can’t be precisely determined by using indirect coupling method. By using the direct- coupled method,the gear heat- structure coupling analysis is carried out,the gear dynamic temperature field and stress distribution are got,and the influence of the friction factor,relative speed,gear modulus on coupling effect are discussed. The results show that the influence of gear modulus on engagement temperature,thermal stress is greater,when the large modulus gear design,the heat- structure coupling effect need to be considered.